Evaluasi Kebijakan E-System dalam Meningkatkan Pelayanan Kepada Wajib Pajak di UPT Pengelola Pendapatan Daerah Malang Utara dan Batu Kota - Sun’an Juhandi, Ali; Ferriswara, Dian (Soetomo Magister Ilmu Administrasi, 2025)
This research aims to evaluate the policy of implementing an online payment system (e-system) in supporting services to taxpayers at the Regional Revenue Management UPT of North Malang and Batu City. The e-system is one of UPT’s priority programs in order to increase taxpayer compliance in fulfilling tax obligations. This research uses a qualitative approach with data collection techniques through observation, interviews and documentation. The evaluation results show that in general the performance of the e-system program is considered sufficient to meet the objectives of simplifying and speeding up services to taxpayers. This can be seen from the increase in the number of online tax payments and the use of online consultation services. However, there are still several aspects that need to be improved, such as limited features, low community digital literacy, and uneven internet access in service areas. Factors supporting the success of the program include ICT infrastructure support and collaboration with related parties. Meanwhile, inhibiting factors include the low level of digital literacy in society and the uneven distribution of internet connections. To increase the benefits of the program, it requires optimizing cooperation, developing features, more intensive socialization, and continuous improvement.